The challenge of translating ischemic conditioning from animal models to humans: the role of comorbidities - Kieran McCafferty; Suzanne Forbes; Christoph Thiemermann; Muhammad M. Yaqoob (The Company of Biologists, 2014)
Following a period of ischemia (local restriction of blood supply to a tissue), the restoration of blood supply to the affected area causes significant tissue damage. This is known as ischemia-reperfusion injury (IRI) and is a central pathological mechanism contributing to many common disease states. The medical complications caused by IRI in individuals with cerebrovascular or heart disease are a leading cause of death in developed countries. IRI is also of crucial importance in fields as diverse as solid organ transplantation, acute kidney injury and following major surgery, where post-operative organ dysfunction is a major cause of morbidity and mortality. Given its clinical impact, novel interventions are urgently needed to minimize the effects of IRI, not least to save lives but also to reduce healthcare costs. In this Review, we examine the experimental technique of ischemic conditioning, which entails exposing organs or tissues to brief sub-lethal episodes of ischemia and reperfusion, before, during or after a lethal ischemic insult. This approach has been found to confer profound tissue protection against IRI. We discuss the translation of ischemic conditioning strategies from bench to bedside, and highlight where transition into human clinical studies has been less successful than in animal models, reviewing potential reasons for this. We explore the challenges that preclude more extensive clinical translation of these strategies and emphasize the role that underlying comorbidities have in altering the efficacy of these strategies in improving patient outcomes.